Novel dehydroepiandrosterone troche supplementation improves the serum androgen profile of women undergoing in vitro fertilization - Keane, Kevin; Hinchliffe, P.; Namdar, N.; Conceicao, J.; Newsholme, Philip; Yovich, John (2015)
Dehydroepiandrosterone (DHEA) is the most abundant steroid hormone in the circulation and has potent multifunctional activity. Epidemiological evidence suggests that levels of serum DHEA decrease with advancing age, and this has been associated with onset or progression of various age-related ailments, including cognitive decline and dementia, cardiovascular disease, and obesity. Consequently, these findings have sparked intense research interest in DHEA supplementation as an “antiaging” therapy. Currently, DHEA is being used by 25% of in vitro fertilization (IVF) clinicians as an adjuvant in assisted reproductive programs, yet the therapeutic benefit of DHEA is unclear. Here, we examined the use of novel DHEA-containing oral troches in patients undertaking IVF and investigated the impact of these troches on their serum androgen profile. This retrospective study determined the androgen profile of 31 IVF patients before (baseline) and after DHEA supplementation (with DHEA). Baseline serum measurements of testosterone (total and free), DHEA sulfate (DHEAS), sex hormone-binding globulin (SHBG), and androstenedione were made before and after supplementation. Each patient received DHEA troches containing 25 mg of micronized DHEA, and troches were administered sublingually twice daily for a period of no greater than 4 months. Adjuvant treatment with DHEA boosted the serum concentration of a number of androgen-related analytes, including total and free testosterone, androstenedione, and DHEAS, while serum SHBG remained unchanged. Supplementation also significantly increased the free-androgen index in IVF patients. Interestingly, the increase in serum analyte concentration following DHEA supplementation was found to be dependent on body mass index (BMI), but not individual age.Patients with the lowest BMI (<20.0 kg/m2) tended to have lower testosterone and DHEAS, but higher SHBG and androstenedione levels in comparison with other BMI groups postsupplementation. However, patients in the highest BMI group (>30.0 kg/m2) tended to have lower androgen responses following DHEA supplementation, but these were not statistically different from the corresponding baseline level. This method of DHEA administration results in a similar enhancement of testosterone, DHEAS, and androstenedione levels in comparison with other methods of administration. Furthermore, we showed that BMI significantly influences DHEA uptake and metabolism, and that BMI should be carefully considered during dosage calculation to ensure a significant and robust androgen-profile boost.